The homogeneous structure in a Cartan space - Mazėtis, Edmundas (Lietuvos matematikos rinkinys, 2013)
The homogeneus almost product structure on the Finsler space have Lieviu Popescu studied. In this paper we study the integrability conditions for the homogeneus product structure in Cartan space with Miron connection.
Keywords: Cartan space; affine connection; homogeneus almost product structure; Nijenhuis tensor